Physicochemical and antimicrobial properties of citral and quercetin incorporated kafirin-based bioactive films. (1st February 2015) - Giteru, Stephen Gitonga; Coorey, Ranil; Bertolatti, Dean; Watkin, Elizabeth; Johnson, Stuart; Fang, Zhongxiang
Highlights: Citral and quercetin were incorporated into kafirin films. Citral decreased the tensile strength and increased the elongation at break. Citral and quercetin both lowered the film oxygen permeability. Kafirin-citral films exhibited the highest antimicrobial activity. Kafirin films have potential as bioactive packaging to improve food safety/quality. Abstract: The aim of this study was to determine the physicochemical and antimicrobial properties of kafirin-based bioactive films incorporating the plant essential oil citral and the polyphenol quercetin. The addition of quercetin and citral both imparted a yellowish colour to the films. The tensile strength of films significantly decreased and elongation at break increased when citral was incorporated, whereas addition of quercetin did not alter these two film parameters. The rate of water vapour transmission of the films decreased with citral incorporation but the water vapour permeability was not affected by either citral or quercetin incorporation. Furthermore, incorporation of citral and quercetin significantly lowered the oxygen permeability of the films. Film made of kafirin alone had antimicrobial activity against Listeria monocytogenes, however, films incorporating citral exhibited the highest antimicrobial activity against Campylobacter jejuni, L . monocytogenes, and Pseudomonas fluorescens . These results suggest that kafirin-based films incorporating citral and quercetin have potential as bioactive packaging to improve food safety and quality.